(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Pediatric traumatic orbital injuries have a number of clinical and CT features. Purpose: To assess the clinical and CT features of pediatric orbital fractures and the influence of these features on the choice among treatment options, and to develop practical recommendations on the basis of the review of long-term treatment outcomes for this type of trauma. Material and Methods: Medical records and CT scans of 27 pediatric patients with orbital wall fractures were retrospectively reviewed. We reviewed traumatic event circumstances, patient age and gender, type and frequency of clinical symptoms, terms and extent of care provided, and CT findings. Results: The most common clinical symptom was diplopia (55.5%). Limited eye movement was found in 37%, and enophthalmos, in 44.4% of patients. Trapdoor fractures were found in 51.9% of patients. Conclusion: The major clinical signs of pediatric orbital wall fractures were diplopia and limited upward eye movement. Trapdoor fracture was the most common type of orbital injury among patients of this study. Because radiography showed no evidence of impairment of orbital wall bones in 22.2% of patients of this study, findings of clinical examination become essential evidence in the diagnosis of pediatric fractures. Time of care provision and active surgical management are important when treating pediatric patients with orbital fractures.